THE EFFECTS OF PROBLEM-BASED LEARNING METHOD ON STUDENTS’ LEARNING INDEPENDENCE OF CHEMISTRY LEARNING IN HIGH SCHOOL - Suyanta Suyanta; Endang W. Laksono; Novia Fitri Fadhilah; Ihwan Rizky (Jurnal Kependidikan, 2019)
Chemistry learning in high school that trains and develops students’ self-sufficiency and independence has not been done optimally because learners still depend on getting information and knowledge from teachers. Problem-based learning method used in the teaching and learning process is expected to facilitate students’ with self-reliance and learning independence. This method is a problem-oriented learning method that makes students be accustomed to solving problems in order to train their ability in discoveringa concept in the learning process. Teaching learning process with PBL model is done for the subject matter of acid base solution and electrolyte non electrolyte solution. Learning independence assessed in this study were self-management, motivation, and confidence. The data of the study were in the form of descriptive quantitative data and analyzed using Anava / Anacova test. The research findings showed that there was a difference of students’ learning independence through the application of problem-based learning method and control method in teaching and learning process.